MAINTENANCE OF HOKKIEN LANGUAGE BY ITS SPEAKERS IN MEDAN - Wijaya, Linda; Saragih, Amrin; Zainuddin, Zainuddin (Association of Language Teachers in Southeast Asia (ALTSA), 2020)
Indonesia is famous for various culture that attracts many tourists from several part of the world to have a visit. Besides having numerous culture, Indonesia is flourished with different ethnics, too, such as the Javanese, the Bataknese, the Indian and the Chinese. Every ethnic speak with different language, but formally the national language is Indonesian language. In this study, the researcher, who derives from Chinese ethnic and resides in Medan, has taken interest in preserving her mother tongue which is Hokkien language. Hokkien language is an informal language which is used by the Hokkien speakers to communicate with one another. In maintaining language, the researcher focuses on the phenomena that happens lately, the researcher feels that Hokkien language is not important for some of the young family in Medan, they teach their children the other language that develops immensely throughout people life. Even though some still maintain Hokkien language, the researcher feels that children do not put any interest in speaking their mother tongue. This will give negative impact to the language existence. The problem in this study is concerned with factors influencing the preservation of Hokkien language. The presentation of the data described in qualitative descriptive method and this study conducted through field survey with interviews and observation. The findings revealed that there are two kinds of language maintenance between young speakers and old speakers. The former has lesser effort in maintaining the language, while the latter has stronger effort. Despite the difference, all of Hokkien speakers still make use of the language in their daily activities. Other factors are the language status of Hokkien language as the mother tongue as well as the identity of Hokkien ethnic, the pride of the culture, and the solidary among Hokkien speakers.